Long non-coding RNA expression profiling in the lesional tissue and derived fibroblasts of keloid - Yuan, Chunyu; Bu, Wenbo; Li, Li; Zhang, Mengli; Chen, Kun; Fang, Fang; Li, Min; Chen, Xu; Gu, Heng (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Long non-coding RNA (lncRNA) plays a key role in various disorders. However, its role in keloid is still unclear. Aim : We explored differentially expressed (DE) lncRNAs and mRNAs between keloid tissue (KT)s and normal tissue (NT)s, as well as keloid fibroblast (KFB)s and normal fibroblast (NFB)s, respectively. Material and methods : We use KTs and NTs from the chest of 5 patients, and 3 pairs of KFBs and NFBs, to perform microarray respectively. Gene ontology and pathway analyses were conducted by online software DAVID (Database for Annotation, Visualization and Integrated Discovery). The validation of targeted lncRNAs were conducted by qRT-PCR in enlarged samples (79 KTs and 21 NTs). Results : We identified 3680 DE-lncRNAs in tissue essay, and 1231 DE-lncRNAs in cell essay. Furthermore, we found that many lncRNAs and their relative mRNAs were regulated simultaneously in keloid. We identified that ENST00000439703 and uc003jox.1 were up-regulated in both of the above essays through comparing the results of lncRNA screening between tissue essay and cell essay; the results were confirmed through qRT-PCR in enlarged samples. Conclusions : Our study demonstrates that numerous lncRNAs are involved in the pathogenesis and development of the keloid.